(untitled) (JURNAL PROTEKSI KESEHATAN, 2020)
Changes in social trend make many women pursue the career, thus storing breastmilk cannot be avoided if Hypercholesterolemia is a condition in which increased cholesterol levels that exceed normal limits, which have a risk of death of coronary heart disease. Aloe vera is a medicinal plant in Indonesia that is often used by the community as tradisional medicine. Compounds contained in Aloe vera namely phytochemicals that contain phenolics compounds. This study aims to determine the effect of aloe vera boiled water with pre and postest research methods. T-tes statiscal results obtained an average value of cholesterol level before treatment of 206,34 mg/dL and an average after treatment 182,43 mg/dL, meaning that there are differences in the results of cholesterol levels before and after consuming Aloe vera boiled water. Then it can be concluded that there is a siginicant effect on the provision of Aloe vera boiled water on the reduction of cholesterol levels in obese respondents level with the p value <0,05.